Sighting of a Southern elephant seal Mirounga leonina in the Toltén River, southern Chile - Sepúlveda, Maritza; Pavez, Guido; Harrod, Chris; Gomez-Uchida, Daniel (Revista de Biología Marina y Oceanografía, 2019)
The Southern elephant seal (SES) is a marine species that can be found at sea throughout the Southern Ocean on most sub-Antarctic islands. An unusual record of a solitary Southern elephant seal (Mirounga leonina) in freshwater habitat is reported. The seal was found 16 km upstream from the mouth of the Toltén River, in southern Chile (39°9’S; 73°10’W). The individual was classified as a sub-adult male approximately 3 m in length. Potential causes for the unusual presence of the seal in a river include feeding on native estuarine fishes and non-native Chinook salmon or resting. Long lasting resting (5 days) in the Toltén River by the seal may indicate suitable habitat and/or lack of disturbance.